1982
DOI: 10.1099/00207713-32-3-358
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Patterns of Proteins in the Genus Bifidobacterium and Proposal of Four New Species

Abstract: The polyacrylamide gel electrophoretic patterns of soluble cellular proteins from 1,094 strains of bifidobacteria were compared with available deoxyribonucleic acid (DNA)-DNA homology data and with the phenotypic and biochemical reactions of these strains. There was excellent correlation between the 25 distinct protein patterns and 24 DNA-DNA homology groups in the genus. Differentiation among species on the basis of common phenotypic properties often was unreliable. Our results demonstrate that the species pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 10 publications
2
46
0
1
Order By: Relevance
“…B. longum JCM 1217 encodes a number of candidates for the ␣-L-arabinofuranosidase gene, 11 members of the GH43 gene family, and 4 members of the GH51 gene family. Several reports indicate that B. longum has the ability to grow on L-arabinose and ␣-L-arabinooligosaccharides (14,23,(25)(26)(27). We showed that B. longum also uses ␤-Ara 2 as a carbohydrate source (supplemental Table S4).…”
Section: Discussionmentioning
confidence: 56%
“…B. longum JCM 1217 encodes a number of candidates for the ␣-L-arabinofuranosidase gene, 11 members of the GH43 gene family, and 4 members of the GH51 gene family. Several reports indicate that B. longum has the ability to grow on L-arabinose and ␣-L-arabinooligosaccharides (14,23,(25)(26)(27). We showed that B. longum also uses ␤-Ara 2 as a carbohydrate source (supplemental Table S4).…”
Section: Discussionmentioning
confidence: 56%
“…(7, 8 , 13). Taxonomic groupings based on PAGE of proteins closely resemble groupings based on DNA-DNA homology data (1,15).…”
mentioning
confidence: 87%
“…PAGE of soluble proteins can be used to differentiate closely related bacteria (1,11,13,17) and has been used to show differences among strains of Actinomyces spp. (7, 8 , 13).…”
mentioning
confidence: 99%
“…Therefore, most of the L-arabinose is thought to utilize by intestinal bacteria. Many reports indicate that B. longum has the ability to grow in the presence of L-arabinose (12,(35)(36)(37). B. longum JCM 1217 encodes a number of candidates for the α-L-arabinofuranosidase gene, 11 members of GH43 gene family, and 4 members of GH51 gene family.…”
Section: G Effects Of Polysaccharides and Hrgps Containing L-arabinomentioning
confidence: 99%